Data Mining for Identifying Novel Associations and Temporal Relationships with Charcot Foot. (27th April 2014) - Munson, Michael E.; Wrobel, James S.; Holmes, Crystal M.; Hanauer, David A.
Abstract : Introduction . Charcot foot is a rare and devastating complication of diabetes. While some risk factors are known, debate continues regarding etiology. Elucidating other associated disorders and their temporal occurrence could lead to a better understanding of its pathogenesis. We applied a large data mining approach to Charcot foot for elucidating novel associations. Methods . We conducted an association analysis using ICD-9 diagnosis codes for every patient in our health system (n = 1.6 million with 41.2 million time-stamped ICD-9 codes). For the current analysis, we focused on the 388 patients with Charcot foot (ICD-9 713.5). Results . We found 710 associations, 676 (95.2%) of which had a P value for the association less than 1.0 × 10 − 5 and 603 (84.9%) of which had an odds ratio > 5.0. There were 111 (15.6%) associations with a significant temporal relationship P < 1.0 × 10 − 3 . The three novel associations with the strongest temporal component were cardiac dysrhythmia, pulmonary eosinophilia, and volume depletion disorder. Conclusion . We identified novel associations with Charcot foot in the context of pathogenesis models that include neurotrophic, neurovascular, and microtraumatic factors mediated through inflammatory cytokines. Future work should focus on confirmatory analyses. These novel areas of investigation could lead to prevention or earlier diagnosis.